2018
DOI: 10.1029/2017ja024954
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Magnetosheath High‐Speed Jets on the Magnetosphere and Ionosphere Measured by Optical Imaging and Satellite Observations

Abstract: Magnetosheath high-speed jets (HSJs) are dayside upstream transient disturbances with enhanced flow velocity and dynamic pressure. They are associated with significant magnetopause perturbations, ultralow frequency waves in the dayside magnetosphere, and localized flow enhancements in the ionosphere. However, whether HSJs have corresponding dayside aurora signatures is still an open question. If auroral signatures are found, 2-D structure and evolution of HSJ effects on the magnetosphere can be imaged in a muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 57 publications
2
50
0
1
Order By: Relevance
“…To summarize, our results suggest that the quasi-parallel and the boundary jets are the classes connected to jet-related phenomena, such as the throat aurora (Han et al, 2017;Wang et al, 2018), magnetopause reconnection (Hietala et al, 2018) and possibly the radiation belts (Turner et al, 2012;Xiang et al, 2016). Finally, both Qpar and boundary jets exhibit high earthward velocities and duration, making them important to investigate magnetosphere coupling phenomena and geoeffective properties.…”
Section: Quasi-parallel and Boundary Jetsmentioning
confidence: 61%
See 1 more Smart Citation
“…To summarize, our results suggest that the quasi-parallel and the boundary jets are the classes connected to jet-related phenomena, such as the throat aurora (Han et al, 2017;Wang et al, 2018), magnetopause reconnection (Hietala et al, 2018) and possibly the radiation belts (Turner et al, 2012;Xiang et al, 2016). Finally, both Qpar and boundary jets exhibit high earthward velocities and duration, making them important to investigate magnetosphere coupling phenomena and geoeffective properties.…”
Section: Quasi-parallel and Boundary Jetsmentioning
confidence: 61%
“…Furthermore, they can affect the radiation belts through the loss of outer belt electrons, (Turner et al, 2012;Xiang et al, 2016). Additionally, jets can affect the aurora via the mechanism of "dayside throat aurora" which has been connected to magnetosheath particle precipitation (Han et al, 2017;Wang et al, 2018). The link between jets and energy transfer through the magnetosphere was also observed recently when surface eigenmodes were found to be excited through a collision between a jet and the magnetopause (Archer et al, 2019).…”
Section: Introductionmentioning
confidence: 88%
“…For example, Hietala et al (2018) published observational evidence of a jet triggering magnetic reconnection at the dayside magnetopause. Wang et al (2018) showed direct correspondence between magnetosheath jets and diffuse and discrete auroral brightenings. The newly observed magnetopause surface eigenmodes (standing waves) were also excited by a jet colliding into the magnetopause (Archer et al, 2019).…”
Section: Introductionmentioning
confidence: 81%
“…Such compression can also excite eigenmodes of the magnetopause surface (Archer et al, 2019). The perturbation on the magnetopause surface can then result in compressional low-frequency waves within the magnetosphere, ionospheric flow enhancements, and auroral brightening (e.g., Archer et al, 2013;Hietala et al, 2012;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%